Memory-enhancing properties of hypericum scabrum essential oil in a rat model of dementia - Sur, Tariq Mohammed; Akbaba, Emel; Bagci, Eyup (Iranian Association of Pharmaceutical Scientists, 2019)
Hypericum species are known to be used in traditional therapies. H. scabrum L. is one of the Hypericum species distributed in Turkey. In this study, we evaluated the effects of Hypericum scabrum essential oil inhalation on spatial memory in scopolamine-induced amnesic rats. The essential oil was characterized by GC-FID and GC-MS system. Male wistar rats were divided into 6 groups: control; scopolamine-alone treated; diazepam-treated (positive control); tramadol-treated (positive control); scopolamine with Hypericum scabrum essential oil 1%-treated; and scopolamine with Hypericum scabrum essential oil 3%-treated group. All rats were tested behaviorally to evaluate spatial memory peformances in Y-maze task and radial-arm maze task. The most abundant component of the essential oil was identified as ?-pinene (51.3%). Hypericum scabrum essential oil application significantly improved spatial memory as compared to scopolamine-alone treated rats as evidenced by increases in spontaneous alternation behavior in Y-maze task and decreases in the number of working memory errors and reference memory errors in the radial-arm maze task in this study. Hypericum scabrum essential oil inhalation could be used as a complementary therapy to reduce memory impairments in the patients with dementia and related diseases. © 2019, Iranian Association of Pharmaceutical Scientists. All rights reserved.
Keywords: Alpha-pinene; Hypericum scabrum essential oil; Memory; Radial-arm maze; Scopolamine; Y-maze